Preventing Packet Dropping Attack in Ad hoc Networks Using Malicious node Isolation Model - Madhurikkha, S; Kumari, C Meenu; Revathi, S; Nathiya, P (International Journal of Computer Sciences and Engineering, 2015)
Securing ad hoc network is one of the trending issues that is going on in the networking industry which has lead to the development of various algorithms and methods for identifying intrusions. Intrusions are of various types namely packet forwarding attack, black hole, sequence numbers etc., there are still so many such intrusions that are taking place. The proposed project is to study the impact of a malicious node in the ad hoc network. The proposed system uses MNI-AODV algorithm by using malicious node isolation(MNI) method. In this paper methods against malicious node is implemented by introducing MNI-AODV in the ad hoc network [7]. The impact of nodes in the presence of packet dropping attack is also presented.